Impact of Sleep Deprivation on Surgical Laparoscopic Performance in Novices: A Computer-based Crossover Study. Issue 3 (June 2019) - Leu, Svenja; Staerkle, Ralph F.; Gaukel, Stefan; Fink, Lukas; Soll, Christopher; Aasen, Davis M.; Liechty, Kenneth; Vitz, Martina; Ramseier, Leonhard E.; Vuille-dit-Bille, Raphael N.
Abstract : Objective: The 24-hour work shifts are newly permitted to first-year surgical residents in the United States. Whether surgery novices' motor activity is affected by sleep deprivation is controversial. Materials and Methods: This study assesses sleep deprivation effects in computer-simulated laparoscopy in 20 surgical novices following 24 hours of sleep deprivation and after resting using a virtual-reality trainer. Participants were randomly assigned to perform simulator tests either well rested or sleep deprived first. Results: Of 3 different tasks performed, no significant differences in total time to complete the procedure and average speed of instruments were found. Instrument path length was longer following sleep deprivation ( P =0.0435) in 1 of 3 tasks. Error rates (ie, noncauterized bleedings, perforations, etc.), as well as precision, and accuracy rates showed no difference. None of the assessed participants' characteristics affected simulator performance. Conclusions: Twenty-four hours of sleep deprivation does not affect laparoscopic performance of surgical novices as assessed by computer-simulation.